Takhrij and Syarah Hadith of Agrotechnology: Benefits of Olives - Qonita Dhiya Farhah Riswahyudi; Wahyudin Darmalaksana; Ahmad Taofik (Gunung Djati Conference Series, 2021)
This study aims to discuss the benefits of olive fruit hadith. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this study are the benefits of olives which have many properties and are highly recommended by the Prophet. The conclusion of this research is takhrij and syarah hadith of the Prophet. About olives with agrotechnology analysis which has many benefits and properties that are beneficial to the body.